Identification of matrix metalloproteinase inhibitors by chemical arrays. Issue 10 (3rd October 2015) - Kawatani, Makoto; Fukushima, Yukako; Kondoh, Yasumitsu; Honda, Kaori; Sekine, Tomomi; Yamaguchi, Yoshiki; Taniguchi, Naoyuki; Osada, Hiroyuki
Abstract: Matrix metalloproteinases (MMPs) are zinc-dependent endopeptidases that degrade many extracellular matrix components and that have been implicated in the pathogenesis of various human diseases including cancer metastasis. Here, we screened MMP-9 inhibitors using photo-cross-linked chemical arrays, which can detect small-molecule ligand–protein interactions on a chip in a high-throughput manner. The array slides were probed sequentially with His-MMP-9, anti-His antibody, and a Cy5-labeled secondary antibody and then scanned with a microarray scanner. We obtained 27 hits among 24, 275 compounds from the NPDepo library; 2 of the identified compounds (isoxazole compound 1 and naphthofluorescein) inhibited MMP-9 enzyme activity in vitro . We further explored 17 analogs of 1 and found that compound 18 had the strongest inhibitory activity. Compound 18 also inhibited other MMPs, including MMP-2, MMP-12, and MMP-13 and significantly inhibited cell migration in human fibrosarcoma HT1080 cells. These results suggest that 18 is a broad-spectrum MMP inhibitor. Graphical abstract: : We identify novel MMP inhibitors using chemical arrays, which detect small molecule–protein interactions on a chip in a high-throughput manner.